Differences between entrepreneurs and managers in large organizations: Biases and heuristics in strategic decision-making - Busenitz, Lowell W.; Barney, Jay B. (Journal of Business Venturing, 1997)
Executive Summary The purpose of this study was to further explore differences between entrepreneurs and managers in large organizations. However, rather than focusing on previously examined individual differences, this study examined differences in the decision-making processes used by entrepreneurs and managers in large organizations. Building on nonrational decision-making models from behavioral decision theory, we asserted that entrepreneurs are more susceptible to the use decision-making biases and heuristics than are managers in large organizations. To understand why entrepreneurs and managers in large organizations may vary in the extent to which they manifest biases and heuristics in their decision- making, it is important to understand the utility of nonrational decision-making. Under conditions of environmental uncertainty and complexity, biases and heuristics can be an effective and efficient guide to decision-making. In such settings, more comprehensive and cautious decision-making is not possible, and biases and heuristics may provide an effective way to approximate the appropriate decisions. The use of heuristics has also been found to be associated with innovativeness. Perhaps a critical difference between these sets of individuals is the extent to which they manifest biases and heuristics in their decision-making. We examined differences between entrepreneurs and managers in large organizations with respect to two biases and heuristics: overconfidence (overestimating the probability of being right) and representativeness (the tendency to overgeneralize from a few characteristics or observations). In this study, entrepreneurs are those who have founded their own firms and are currently involved in the start-up process with the average time since founding of 1.7 years. The analysis for this study involved responses from 124 entrepreneurs. Managers are individuals with middle to upper level responsibilities with substantial oversight in large organizations. To be included in this study, the managers had to oversee at least two functional areas (sample average was 4.55 functional areas). Usable responses were received from 95 managers. The results from the logistic regression analysis show strong support for both hypotheses. Even after controlling for numerous factors, such as several traits and demographic factors, enduring support was found for the way entrepreneurs and managers in large organizations make decisions. Our overconfidence and representativeness variables correctly categorized entrepreneurs and managers more than 70% of the time. Thus, this research indicates that entrepreneurs do behave differently than do managers in large organizations and that these differences are substantial. Practically, we speculate that without the use of biases and heuristics, many entrepreneurial decisions would never be made. With entrepreneurial ventures in particular, the window of opportunity would often be gone by the time all the necessary information became available for more rational decision-making. Additionally, successfully starting a new business usually involves overcoming multiple hurdles. Using biases and heuristics as simplifying mechanisms for dealing with these multiple problems may be crucial. To face such hurdles from a strict econometric approach would not only postpone decisions, but would in all likelihood make them overwhelming. More specifically, overconfidence may be particularly beneficial in implementing a specific decision and persuading others to be enthusiastic about it as well. The use of biases and heuristics may also offer some help in explaining why entrepreneurs sometimes make bad managers. Whereas the use of cognitive biases may be beneficial in some circumstances, it can lead to major errors in others. Although research has yet to establish performance implications, it is possible that the more extensive use of heuristics in strategic decision-making may be a great advantage during the start-up years. However, it may also lead to the demise of a business as a firm matures.